Stunting prevention efforts through integrative socialization and counseling programs in Karangwangi Village Cianjur Regency - Setiavi, Shafira Rahmayanti; Julyandini, Tania (Dedicated: Journal of Community Services (Pengabdian kepada Masyarakat), 2024)
In 2016, stunting caused 2.2 million child deaths worldwide. Indonesia ranks 115 out of 151 countries with the highest stunting prevalence globally in 2022. In the West Java region, especially in Cianjur Regency, the stunting rate has decreased from 33.7 percent in 2021 to 13.6 percent in 2022. In Karangwangi Village, Ciranjang District, in 2023, 6 children were found who were indicated to be stunted. Various factors, both direct and indirect factors cause stunting cases. One of the main factors that prevent stunting is the role of a mother. So this service program is realized in the form of stunting socialization which aims to increase awareness of mothers in Karangwangi Village about stunting and clean and healthy living behavior for children as an effort to help realize the creation of individuals with a clean and healthy environment. Both of these programs have been held at Posyandu, PAUD, and also elementary schools located in Karangwangi Village.